Tracheobronchomegaly associated with tracheobronchopathia osteochondroplastica: a case report - Li, Zhen Hua; Kong, Lu-Xia; Zhu, Shan; Hu, Yi; Gao, Shan (Frontiers in Medicine, 2024)
Tracheobronchomegaly (TBM) is a rare condition characterized by the dilatation of the trachea and bronchi due to severe atrophy of elastic fibers, accompanied by the thinning of the muscularis mucosae and the development of diverticula between cartilaginous rings. The etiology of this condition remains unclear. Tracheobronchopathia osteochondroplastica (TO) is another uncommon airway disease with an unknown etiology. The co-occurrence of these two diseases has not been reported. In this study, we report and discuss a case involving an elderly man with TBM and TO with a history of recurrent pneumonia over the past 6 years.